Social, Personal, Cultural and Psychological Influence Analysis of Samsung Smartphone Purchase Decision at Samsung Experience Store WTC Surabaya - Arbi Illyasa; Arasy Alimudin (LPPM NAROTAMA UNIVERSITY, Indonesia, 2018)
Quality human resources are needed in obtaining the success of the company. This study aims to determine the analysis of social, personal, cultural and psychological influences on purchasing decisions of Samsung smartphones in Surabaya. The type of research used is quantitative research with a sample of 50 people who bought at Samsung Experience Store in Surabaya who filled out questionnaires which were already recorded customers. The data analysis technique used is multiple linear regression analysis. The results of the study show that social, personal, cultural and psychological influences simultaneously on purchasing decisions in Surabaya. As well as social, personal, cultural and psychological influences partially on the purchasing decisions of Samsung experiene store smartphones in Surabaya. The higher the social, personal, cultural and psychological well the higher the level of purchasing decisions.